KUALITAS UDARA DALAM RUANG DI DAERAH PARKIR BASEMENT DAN PARKIR UPPERGROUND (STUDI KASUS DI SUPERMARKET SEMARANG) - Huboyo, Haryono Setiyo; Istirokhatun, Titik; Sutrisno, Endro (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2016)
Ever increasing building growth in urban areas is limited by land availability. Lack of space in this area lead to build high rise building rather landed building. In this type of building, parking area  is  built  in  the  basement  and  or upperground  inside  the  building.  Within  this  enclosed space,  indoor  air quality  might  a  problem.  This  study  focus  to  compare  emerged pollutants between  basement  parking  area  and  upperground  parking  area in  supermarket  building.  The dust  sampler,  the  impinger  and  the  CO monitor  were  used  to  measure  TSP,  NO 2   and  CO concentrations respectively  in  these  areas  during  supermarket  operations.  In  the basement area,  in  particular,  the  TSP  concentrations  tend  to  exceeds  300 µg/m 3   mainly  at  weekend period. While for NO 2  and CO concentrations still meet the air quality standard. Based on these findings it seems the main source of pollutants was derived from dust resuspension. Thus, the mitigation measures to reduce this dust resuspension should be emphasized in order to prevent air quality deterioration in the basement parking area.